Impact of Corona Virus on Criminal Action and Prevention Measures in Indonesia - I Ketut Seregig; Bambang Hartono; Budi Waskito (Fakultas Hukum, Universitas Warmadewa, 2020)
This article is data obtained from interviews with traders in traditional and modern markets about the impact of criminal acts due to the corona virus outbreak in Indonesia. The data is supported by secondary data collected from official sources, among others published by the ministry of trade and other social media. The purpose of writing this article is to provide input on a corona virus epidemic prevention plan and mitigate the impact of criminal acts due to hoax news related to corona virus outbreaks. The impact of the corona virus outbreak in the community is the accumulation of protective masks that cause the price of masks to rise in the market, the spread of hoaxes by people who are not responsible, among others; hoax news with the contents